Repair of pre-cracked aluminium alloy panel with CFRP bonded patch and its comparison with riveted patch. (2023) - Kadam, Shubham; Kumar, Prashant; Shinde, Hanmant
Abstract: A thin skin of an aluminium alloy 6061-T6 with a centre pre-crack was repaired by using two methods: i) bonding a CFRP patch, and ii) attaching an Al 6061-T6 patch with the help of rivets. The specimen was subjected to a fatigue load of stress ratio = 0.1 with maximum stress equal to half of the yield stress of the Al 6061-T6 specimen. Numerical simulation results show that the performance of the repair with a bonded CFRP patch was as good as that of the aluminium alloy patch attached through riveting.